Jonah—A Quest to Identify its Genre: Festschrift for Gert Prinsloo - Potgieter, Henk (Journal for Semitics, 2023)
Considering the brevity of Jonah, or perhaps because of it, it is remarkable that the literary genre of the book remains an enigma. This is not the result of a lack of attempts to classify it. Most scholars agree that Jonah is a narrative, but what type of narrative? This article proposes that Jonah is a narrative about a specific episode in a prophet’s life, namely his flight from an assignment. To verify the possibility of such a literary category, one must find similar incidents in other known prophets’ lives and compare Jonah with those episodes. Consequently, a comparison is made with the story of Moses in Exodus and Elijah in 1 Kings 19.